Perceived enjoyment and peer influence on adoption of virtual reality in higher education - Xiaojing Jiang; Md Gapar Md Johar; Jacquline Tham (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Virtual reality (VR) exhibits substantial educational potential, but its adoption rate among Chinese students in higher education institutions remains low, with a lack of empirical research on influencing mechanisms, especially in regions like Nantong. This study constructed a model based on the unified technology acceptance and use theory 2 (UTAUT2), and collected 402 sample data from students of Nantong higher education institutions. An empirical study was conducted using the structural equation model (SEM). The results showed that perceived enjoyment (intrinsic motivation) and peer influence (extrinsic motivation) were positively correlated with the willingness to use VR and the adoption of VR. The willingness to use played a partial mediating role. This study innovatively proposed the synergistic driving effect of intrinsic motivation and extrinsic motivation in the context of higher education in China, and provided practical guidance for the promotion of VR in higher education.